PEMIKIRAN JASSER AUDA MENUJU MAQASYID SYARIAH KONTEMPORER - Busri, Busri; Selamet, Selamet; Luqman, luqman (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2025)
Jasser Auda's thoughts begin with a critique of Ushul fiqh. This research answers first, Ushul al-Fiqh tends to be textual and ignores the purpose of the text; second, the classification of several ulus al-Fiqh theories leads to binary and dichotomous logic; third, the analysis of al-Fiqh's proposals is reductionist and atomistic. Apart from that, Jasser Auda also criticized the classic Maqasid which was too focused on individual benefit so that it was unable to answer current global problems. Therefore, Jasser Auda expands the scope and dimensions of classical maqasid theory to answer the challenges of modern times. This research uses a qualitative method with a descriptive approach. This research produces Jasser Auda's theory, namely system as an approach in Islamic law, and develops a set of categories using six system features, namely cognitive nature, interconnectedness, wholeness, openness, multidimensionality, and meaningfulness. This research also reveals the figure of the Contemporary Maqasyid syariah Thinker where He did not eliminate the maqasyid of Classical Sharia, he only developed it to suit the needs of today's society. This research is considered important in current developments with growing legal needs.